Mapping volumes to planes: Camera-based strategies for snapshot volumetric microscopy - Engelhardt, Moritz; Grußmayer, Kristin (Frontiers in Physics, 2022)
Optical microscopes allow us to study highly dynamic events from the molecular scale up to the whole animal level. However, conventional three-dimensional microscopy architectures face an inherent tradeoff between spatial resolution, imaging volume, light exposure and time required to record a single frame. Many biological processes, such as calcium signalling in the brain or transient enzymatic events, occur in temporal and spatial dimensions that cannot be captured by the iterative scanning of multiple focal planes. Snapshot volumetric imaging maintains the spatio-temporal context of such processes during image acquisition by mapping axial information to one or multiple cameras. This review introduces major methods of camera-based single frame volumetric imaging: so-called multiplane, multifocus, and light field microscopy. For each method, we discuss, amongst other topics, the theoretical framework; tendency towards optical aberrations; light efficiency; applicable wavelength range; robustness/complexity of hardware and analysis; and compatibility with different imaging modalities, and provide an overview of applications in biological research.